Integrability of non-linear differential equations; lax formulation and bi-Hamiltonian structures - Güntürk, Kamil Serkan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Sciences and Engineering, 1998., 1998)
The integrability of non-linear differential equations are studied on the basis of Lax and bi-Hamiltonian formulations. The relations between the Lax formalism and bi-Hamiltonian structures are analysed and illustrated with well known examples such as the KdV system. Various methods resulting from this analysis are then applied to multicomponent KdV equations.
Keywords: Korteweg-de Vries equation.; Differential equations, Nonlinear.; Hamiltonian systems.